Airway calibre as a confounder in interpreting bronchial responsiveness in asthma. Issue 9 (September 1992) - Dirksen, A; Madsen, F; Engel, T; Frølund, L; Heinig, J H; Mosbech, H
Abstract : BACKGROUND: The relation between airway responsiveness to constrictor agents and forced expiratory volume in one second (FEV1) is important when interpreting change in airway responsiveness after an intervention. The aim of the study was to analyse the relation between FEV1 as a percentage of predicted values (% predicted) and airway responsiveness between and within asthmatic subjects. METHODS: Results of non-specific bronchial challenge tests were pooled from two randomised crossover studies comparing the effect of a non-sedative antihistamine with placebo in 35 patients with moderate asthma. The design of the two studies was similar: the provocative concentration of either histamine (first study) or methacholine (second study) resulting in a 20% decrease in ventilatory capacity (PC20) was repeated at two week intervals while patients were treated with the antihistamine or placebo. The dose of inhaled corticosteroid was gradually reduced during the study. Data were analysed with PC20 as the dependent variable in a general linear model so that the influence on PC20 of inhaled corticosteroid dose, antihistamine, and choice of bronchoconstricting agent could be separated from the influence of FEV1% predicted. RESULTS: The correlation coefficient between mean PC20 and mean prechallenge FEV1 for each patient was 0.45. In the general linear model two thirds (65%) of the variation in PC20 was due to variation between subjects. One third of the within subject variation in PC20 could be explained by variation in prechallenge FEV1% predicted (a change in FEV1 of 27% predicted was associated with one doubling or halving of PC20). Treatment with the antihistamine had no influence on PC20, except when histamine was used as the bronchoconstricting agent. The dose of inhaled corticosteroid had a small but significant effect. CONCLUSIONS: The variation in a patient's PC20 over time (several months) is related to changes in FEV1% predicted. Variation in FEV1% predicted explains less of the variation in bronchial responsiveness between subjects where a patient specific factor, which is probably related to the pathogenesis of bronchial asthma, seems to dominate.